A SUCCESSFUL STRATEGY OF POLITICAL PARTY CAMPAIGN AHEAD OF ELECTION IN DEVELOPED COUNTRIES - Linayati Lestari; Askarmin Harun; Amrullah Rasal; Ronald Parlindungan; Fajarina Nur Fatiha; Susanto Susanto (Universitas Riau Kepulauan, 2023)
This study aims to analyze the arts performed by political parties before the democratic era of disruption. Information and communication technology development has forced political parties to be enthusiastic about using the internet, including social media. The internet and social media are inseparable; social media is a nomenclature of the communication art of political parties that goes according to their wishes. This study uses a qualitative data analysis software approach (QDAS) and bibliometrics with the help of VosViewer and Nvivo 12 software. The research data sources use 428 articles from the Scopus database. The data search phase uses the keywords